Once More . . (Reviews in religion and theology, 2003)
Mark S. Smith, Second Edition with a foreword by Patrick D. Miller, The Early History of God: Yahweh and the Other Deities in Ancient Israel Martin Buber, ed. Maurice S. Friedman, Third Edition, Meetings: Autobiographical Fragments Martin Buber, The Legend of the Baal-Shem Martin Buber, Ten Rungs: Collected Hasidic Sayings Martin Buber, Between Man and Man Martin Buber, The Way of Man According to the Teachings of Hasidism Maurice S. Friedman, Martin Buber: The Life of Dialogue Ira M. Lapidus, A History of Islamic Societies Gerhard Endress, Islam: An Historical Introduction Henry D. Rack, Reasonable Enthusiast: John Wesley and the Rise of Methodism Adrian Hastings, Alistair Mason and Hugh Pyper (eds), Christian Thought: A Brief History Paul Avis, T & T Clark, Anglicanism and the Christian Church: Theological Resources in Historical Perspective